Characterization and comparison of mixed-mode and reversed-phase columns; interaction abilities and applicability for peptide separation - Kadlecová, Zuzana; Kozlík, Petr; Tesařová, Eva; Gilar, Martin; Kalíková, Květa (Journal of chromatography. A, 2021)
In this work, two mixed-mode columns from a different manufacturers and one marketed as a reversed-phase column were characterized and compared in the terms of their interaction abilities, retentivity, peak symmetry, and applicability for peptide separation. All the tested columns contain octadecyl ligand and positively charged modifier, i.e. pyridyl group for the reversed-phase column XSelect CSH C18, quaternary alkylamine for mixed-mode column Atlantis PREMIER BEH C18 AX, and permanently charged moiety (details not available from the manufacturer) for mixed-mode column Luna Omega PS C18. For detailed characterization and comparison of their interaction potential, several approaches were used. First, a simple Walters test was performed to estimate hydrophobic and silanophilic interactions of the tested columns. The highest values of both parameters were observed for column Atlantis PREMIER BEH C18 AX. To investigate the effect of pH and buffer concentration on retention, mobile phases composed of acetonitrile and buffer (ammonium formate, pH 3.0; ammonium acetate pH 4.7 and pH 6.9) in various concentrations (5mM; 10mM; 15mM and 20mM) were used. The analysis of permanently charged compounds was used to describe the electrostatic interaction abilities of the stationary phases. The most significant contribution of electrostatic interactions to the retention was observed for Atlantis PREMIER BEH C18 AX column in the mobile phase with buffer of pH 3.0. A set of ten dipeptides, three pentapeptides and one octapeptide was used to investigate the effects of pH and buffer concentration on retention and peak symmetry. Each of the tested columns provides the optimal peak shape under different buffer pH and concentration. The gradient separation of the 14 tested peptides was used to verify the application potential of the tested columns for peptide separation. The best separation was achieved within 4 minutes on column Atlantis PREMIER BEH C18 AX.
Keywords: koncentrace vodíkových iontů; hydrofobní a hydrofilní interakce; chromatografie s reverzní fází; Mixed-mode chromatography; Reversed-phase column; Hydrophobic and Hydrophilic Interactions; Chromatography, Reverse-Phase; Peptides; RP/anion-exchange mechanism; peptidy; Hydrogen-Ion Concentration; Mixed-mode columns; Buffers; pufry; Peptide separation